Dupuytren's contracture and occupational exposure to hand-transmitted vibration. - Palmer, K; D'Angelo, S; Syddall, H; Griffin, M; Cooper, C; Coggon, D (2014)
AIMS: The relation between Dupuytren's contracture and occupational exposure to hand-transmitted vibration (HTV) has frequently been debated. We explored associations in a representative national sample of workers with well-characterised exposure to HTV. METHODS: We mailed a questionnaire to 21 201 subjects aged 16-64 years, selected at random from the age-sex registers of 34 general practices in Great Britain and to 993 subjects chosen randomly from military pay records, asking about occupational exposure to 39 sources of HTV and about fixed flexion contracture of the little or ring finger. Analysis was restricted to men at work in the previous week. Estimates were made of average daily vibration dose (A(8) root mean squared velocity (rms)) over that week. Associations with Dupuytren's contracture were estimated by Poisson regression, for lifetime exposure to HTV and for exposures in the past week >A(8) of 2.8 ms(-2) rms. Estimates of relative risk (prevalence ratio (PR)) were adjusted for age, smoking status, social class and certain manual activities at work. RESULTS: In all 4969 eligible male respondents supplied full information on the study variables. These included 72 men with Dupuytren's contracture, 2287 with occupational exposure to HTV and 409 with A(8)>2.8 ms(-2) in the past week. PRs for occupational exposure to HTV were elevated 1.5-fold. For men with an A(8)>2.8 ms(-2) in the past week, the adjusted PR was 2.85 (95% CI 1.37 to 5.97). CONCLUSIONS: Our findings suggest that risk of Dupuytren's contracture is more than doubled in men with high levels of weekly exposure to HTV.